Proceedings of the ACM/SIGDA International Symposium on Field Programmable Gate Arrays 2009
DOI: 10.1145/1508128.1508203
|View full text |Cite
|
Sign up to set email alerts
|

High-performance, cost-effective heterogeneous 3D FPGA architectures

Abstract: In this paper, we propose novel architectural and design techniques for three-dimensional field-programmable gate arrays (3D FPGAs) with Through-Silicon Vias (TSVs). We develop a novel design partitioning methodology that maps the heterogeneous computational resources of an FPGA into a number of die such that the total die area is minimized and the FPGA performance is maximized. Minimizing the total die area leads to direct manufacturing cost savings which is an important incentive to bring 3D technology to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In order to have a detailed path delay analysis and architecture optimization, we used the optimal vertical and horizontal [27] shows 58 % performance improvement. However the paper lacks the hardware infrastructure to experiment and validate the achievement presented in it.…”
Section: Delay Analysis: Heterogeneous Treementioning
confidence: 99%
See 1 more Smart Citation
“…In order to have a detailed path delay analysis and architecture optimization, we used the optimal vertical and horizontal [27] shows 58 % performance improvement. However the paper lacks the hardware infrastructure to experiment and validate the achievement presented in it.…”
Section: Delay Analysis: Heterogeneous Treementioning
confidence: 99%
“…As explained in [4,9,27] the programmable interconnect overhead is main design element to increase the FPGA system performance. The main advantage of horizontally partitioned 3D heterogeneous Tree-based FPGA, is that, it offers design flexibility to optimize the wire length of higher levels of the Tree interconnects.…”
Section: Delay Analysis: Heterogeneous Treementioning
confidence: 99%
“…The architecture definition, partitioning, placement, routing and optimization are performed individually for each netlist listed in Table 1. To make 3D HT-FPGA more efficient in terms of design and manufacturing, it is essential to minimize the TSV count because TSV consumes more silicon area than horizontal interconnects [9,5]. The TSV and architecture optimization are performed based on Rent's parameter [7] "p" defined for a Tree-based heterogeneous architecture as shown in equation 1.…”
Section: Area and Tsv Count Optimizationmentioning
confidence: 99%
“…Nonetheless the number of available TSVs within 3D-SBs is assumed to be fixed and that means the design do not investigate the impact of different numbers of TSVs in a 3D-SB. A mesh-based heterogeneous 3D FPGA architecture optimization is presented in [5]. …”
Section: Introductionmentioning
confidence: 99%
“…In the context of GPPs, interface between the L2 cache and main memory is architected using 3D interconnect technology, and performance is compared to a 2D design for memoryintensive applications [6][7][8][9][10]. In the context of FPGAs, a number of recent studies have shown that 3D FPGAs have better performance than existing 2D designs [11][12][13].…”
Section: Introductionmentioning
confidence: 99%